Farmers' decision making on crop production : a case study of Begnas Village Panchayat in Nepal - Adhikari, Jagannath; Weber, Karl E.; Demaine, Harvey; Osakaya, Yoshiyuki; Gonzales, Jr. R. L.; Government of France (Bangkok : Asian Institute of Technology, 1987)
Farmers' decision making in the context of their farming system in the midhills of western Nepal is described and analyzed. Given the physiographic conditions of the study area, two types of farming pattern are integrated into' one farming system, which was examined from ecological, social and cultural points of view, considering a household as an organizational unit of decision making. The farming system was found affected by all factors mentioned above as they were related to the farming technology developed by farmers. The study of these elements of the farming system showed that farmers were very eager to accept changes in order to improve their conditions. Their traditional farming practices were found appropriate in the context of the present situations, because they aptly served their current strategy of securing food supply for family requirements and utilising their labour throughout the year. In that, the goals and values of distinct categories of farmers differed, as manifest in the variations of types of crops grown and selection of varieties of rice. Pursuing a permanent type of agriculture, farmers are bound by various kinds of obligations. This included obeyance of astrological beliefs and chiliastic expectations which, however, were found not limiting decision making with a view to adoption of modern technology. Recommendations for planning inc lude assorted specific proposals relating to policy making aspects, development strategies for new technologies, extension methods, and improvement of living standard. They are supplemented by a set of pertinent, problem oriented recommendations for further research.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1987
Keywords: Farm management -- Nepal -- Decision making